Embodied Making and Design Learning - Special Issue from the Learn X Design-conference DRS/CUMULUS, Chicago 2015 - Gulliksen, Marte Sørebø; Hondzel, Catharine Dishke; Seitamaa-Hakkarainen, Pirita; Härkki, Tellervo (FormAkademisk, 2016)
This issue of FORMakademisk features selected articles developed from papers presented at the symposium Embodied Making and Design Learning at the DRS/CUMULUS-conference LearnXDesign in Chicago, Illinois, June 28–30, 2015. This special issue was developed as an initiative by the symposium conveners. The symposium was developed by researchers from research groups in Norway, Finland and Canada to explore various aspects of embodied making in relation to design learning. The symposium was a full-day event with four sessions, seven paper presentations, a roundtable discussion, a plenary discussion and a workshop. The symposium received positive feedback, attracting many participants and stimulating engaged discussions throughout the conference. This indicates a growing awareness of the topic of embodied making and design learning. This special issue features five articles that together highlight a variety of approaches and examples of current research endeavours in relation to the theme.